The Influence of Organizational Commitment, Non-Financial Compensation and Organizational Justice on Readiness to Change - Latifah Dwifi Rahayu; Anik Herminingsih (Journal La Sociale, 2024)
This research aims to examine and analyze Organizational Commitment, Non-Financial Compensation and Organizational Justice on Readiness to Change. The population in this research were employees of the Deputy for Human Resources for Science and Technology, the National Research and Innovation Agency. The sample used was 114 people. The sampling method uses a quota sampling model. The data collection method used a survey method, with the research instrument being a questionnaire using a Likert scale as a questionnaire assessment tool. Methods of data analysis using SPSS 26. The results of this research indicate that organizational commitment has a positive effect on readiness to change, non-financial compensation has a positive effect on readiness to change and organizational justice has a positive effect on readiness to change.